Pendidikan Keluarga: Analisis Teologis Membangun Keutuhan dalam Rumah Tangga Kristen - Naftali Edoway (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2022)
The family is a small community that has a major influence on the environment. Building a harmonious environment, starting from family harmony and family cannot be separated from education, where harmony education is the basis in the formation of a good family and the right character according to the word of God. This research aims to explore education in the family in building wholeness in the household. A qualitative method with a literature study approach is used to collect and analyze data. The results of the study explained that a harmonious family education model applied by parents should be a culture that continues to be carried out in building a whole person in a Christian household. Then, the principles of love and peace become the foundation for strengthening the integrity of the Christian family.